Does the primary treatment sequence affect post‐relapse survival in recurrent epithelial ovarian cancer? A real‐world multicentre retrospective study. (9th December 2022) - Liu, Xingyu; Zhao, Yingjun; Jiao, Xiaofei; Yu, Yang; Li, Ruyuan; Zeng, Shaoqing; Chi, Jianhua; Ma, Guanchen; Huo, Yabing; Li, Ming; Peng, Zikun; Liu, Jiahao; et al.
Abstract: Objective: To explore the impact of the primary treatment sequence (primary debulking surgery, PDS, versus neoadjuvant chemotherapy and interval debulking surgery, NACT‐IDS) on post‐relapse survival (PRS) and recurrence characteristics of recurrent epithelial ovarian cancer (REOC). Design: Real‐world retrospective study. Setting: Tertiary hospitals in China. Population: A total of 853 patients with REOC at International Federation of Gynaecology and Obstetrics stages IIIC–IV from September 2007 to June 2020. Overall, 377 and 476 patients received NACT‐IDS and PDS, respectively. Methods: Propensity score‐based inverse probability of treatment weighting (IPTW) was performed to balance the between‐group differences. Main Outcome Measures: Clinicopathological factors related to PRS. Results: The overall median PRS was 29.3 months (95% CI 27.0–31.5 months). Multivariate analysis before and after IPTW adjustment showed that NACT‐IDS and residual R1/R2 disease were independent risk factors for PRS ( p  < 0.05). Patients with diffuse carcinomatosis and platinum‐free interval (PFI) ≤ 12 months had a significantly worse PRS ( p  < 0.001). Logistic regression analysis revealed that NACT‐IDS was an independent risk factor for diffuse carcinomatosis (OR 1.36, 95% CI 1.01–1.82, p  = 0.040) and PFI ≤ 12 months (OR 1.59, 95% CI 1.08–2.35, p  = 0.019). In IPTW analysis, NACT‐IDS was still significantly associated with diffuse carcinomatosis (OR 1.29, 95% CI 1.05–1.58, p  = 0.015) and PFI ≤ 12 months (OR 1.90, 95% CI 1.52–2.38, p  < 0.001). Conclusions: The primary treatment sequence may affect the PRS of patients with REOC by altering the recurrence pattern and PFI duration.